“They are almost humans like us”: indigenous politics and policy dismantling under Bolsonaro’s government - Barros Soares, Leonardo; Grant Baines, Stephen (Revista Videre, 2021)
This paper argues that three ongoing dismantling processes target the Brazilian indigenist policy under Bolsonaro’s government: (1) the dismantling of the land claims recognition policy and institutions; (2) the dismantling of the protection of indigenous lives due to the increasing violence against indigenous peoples and the COVID-19 pandemic; and (3) the dismantling of the integrity of traditional territories related to government plans to open indigenous lands to large-scale agricultural and mining operations. On the other hand, we point out that Brazilian indigenous movements’ contemporary strategies are developing to fight back against the dismantling of indigenist policy. We use primary and secondary data to investigate those topics, discussing them in depth using the policy-dismantling theoretical framework. We conclude by pointing to the fact that the ongoing dismantling may contribute to the genocide of Brazilian indigenous peoples.